INVESTIGATION OF SLIME FORMATION PROCESSES IN TURBINE AND INDUSTRIAL OILS - Матвєєва, О.Л.; Маринич, Т.О. (Proceedings of National Aviation University (archive), 2012)
The problem of operating turbine and industrial oils is to ensure the preservation of physical and chemical properties of oils for a long period of time. It is established that at all stages of operation the oil exposed to various contaminants of dispersed phase, the nature and origin. Chemical analysis of oil contamination shows that up to 70% by weight of contaminants is silicon dioxide and the rest are air, water, “wear and corrosion products” and slime. These contaminants are the main reasons that cause slime formation. Slime is a resinous hydrocarbon residue, in most cases, brown in colour. As a result, slime formation lead to a change the physical and chemical properties of oils, active process of aging, the oil becomes a wastes.